Industry–university engagement in multicultural engineering programs: an exploratory study - Gatson, Jacqueline M. (Kansas State University, 2015)
Facing the rapidly increasing globalization of world economies and a steadily diversifying domestic consumer base, U.S. corporations have embraced the benefits of hiring more employees with diverse perspectives and experiences. Particularly in industries dependent upon knowledge of science, technology, engineering, and mathematics, recognition has grown that the American work force is seriously constrained by the clear underrepresentation of minority participants. In engineering, the most prevalent attempt to address these issues is through the establishment of multicultural engineering programs (MEPs), often designed as partnerships between universities and major corporate entities. These programs strive to identify, recruit, retain, educate and ultimately employ significant numbers of students of color to strengthen industry innovation and competitiveness. This investigation was initiated to expand the limited research literature on MEPs and the nature of their partnerships with industry. Using qualitative methodology, an exploratory viewpoint, and the lens of the Commitment-Trust Key Mediating Variable Model (KMV) of Relationship Marketing, the relationships of five mature and highly regarded university MEPs and one of their self identified primary industry partners were examined. Leaders of the National Association of Multicultural Engineering Program Advocates, the national representative body for MEPs, identified exemplary MEPs in the organization’s five regions; using a selection paradigm, five institutions were chosen for study selected from four of the regions. Each institution then identified a primary industry partner. Participants responded to in-depth interviews (MEPs) and questionnaires (industry) with respect to the nature, benefits, and challenges to both entities in the partnerships. Documents were reviewed for each program and industry. Responses were coded, crosschecked, and analyzed for patterns and themes. In particular, the study explored the issue of how commitment and trust are established in these partnership relationships. Twenty-four patterns and three themes emerged. Clearly, university-industry multicultural engineering partnerships are viewed as engendering important employment opportunities for underrepresented program graduates, promoting a well-developed pipeline of minority employee talent for industry, and increasing funding both for university multicultural programming and minority student support. The study also reports on the broad range of activities these partnerships practice. It suggests avenues for further study to enhance university-industry engagement.
Keywords: University-industry partnerships; Diversity; Science Technology Engineering and Mathematics (STEM); National Association of Multicultural Engineering Program Advocates (NAMEPA); Multicultural Engineering Programs (MEPs); Industry engagement; Educational leadership (0449); Higher Education (0745); Multicultural education (0455)